Malignant myoepithelial tumor of the right fibula in a young female: A case report - Tasneem AbuShaikha; Saja Alzboun; Ameer Alhosheyeh; Imad Aljaafreh; Ahmad Alhalabia; Haytham Shaban; Ahmed Barbarawi; Yazan Haddar; Farah Awad; Elias Edward Lahham (SAGE Open Medical Case Reports)
Myoepithelial tumors are extremely rare tumors, with only about 30 cases reported in the literature to date. We present the case of a 27-year-old female diagnosed with malignant right fibula myoepithelial tumor/myoepithelial carcinoma, initially treated with systemic chemotherapy. During treatment, she developed uncontrolled leg pain and metastatic disease to the lungs, leading to a palliative above-knee amputation. Due to the rarity of malignant myoepithelial tumors and the lack of treatment guidelines, a systematic literature review was conducted, exploring various chemotherapeutic and biological agents. Her treatment was planned by a multidisciplinary team, considering her willingness to continue treatment, and ultimately, a decision was made to proceed with palliative care. This case report aims to provide valuable insights for physicians managing patients with this rare diagnosis.